AN ANALYSIS OF THE MAIN CHARACTER’S SEARCH FOR IDENTITY IN TERE LIYE’S NOVEL SENDIRI: A JUNG PSYCHOANALYTIC PERSPECTIVE - Feryanti Kurnia Andi; Hari Windu Asrini (PT. Jurnal Center Indonesia Publisher, 2026)
This study examines the main character’s search for identity in Tere Liye’s novel Sendiri (2024) through the lens of Carl Gustav Jung’s psychoanalytic theory. The research addresses the lack of in-depth psychological analysis regarding how the protagonist confronts inner conflict, loneliness, and past trauma in the process of identity formation. The study aims to describe the forms, strategies, and obstacles in the character’s identity quest, as well as to analyze the individuation process based on Jungian concepts such as persona, shadow, anima/animus, and the Self. A qualitative descriptive method was employed, utilizing close reading and thematic analysis of textual data from the novel. Findings reveal that the protagonist undergoes a complex, nonlinear psychological journey toward self-understanding, triggered by existential crisis and emotional isolation. Through deep introspection, symbolic interactions (particularly with natural elements like the moon), and confrontation with the shadow, the character gradually integrates fragmented aspects of the self. This study demonstrates that Jungian theory effectively uncovers the psychological depth of characters in contemporary Indonesian literature and affirms the relevance of literary fiction as a medium for reflecting on identity formation and emotional resilience in real life.